Associação das técnicas da microabrasão do esmalte com o clareamento dental na recuperação estética do sorriso: acompanhamento clínico - Gallina, Jéssica da Silva [UNESP] (2014)
This case report presents a clinical protocol for enamel stain removal followed by dental bleaching using carbamide peroxide. The procedures began with enamel macroabrasion of white dental enamel stains using a fine-grained diamond bur (3195 FF K.G. Sorensen). Immediately after, correction of the color pattern, uniformization of dental enamel surface was performed using the Opalustre microabrasive product (Ultradent Products Inc, South Jordan, UT, USA). One month after enamel microabrasion, dental bleaching using 10% carbamide peroxide was performed. As a result, we noticed the effectiveness of the applied techniques for the recovery of our patient's smile aesthetics